2019
DOI: 10.1039/c9en00693a
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of graphene oxide with reactive oxygen species (hydroxyl radical, singlet oxygen, and superoxide anion)

Abstract: Increases in the production and applications of graphene oxide (GO), coupled with reports of its toxic effects, are raising concerns about its health and ecological risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 49 publications
(61 reference statements)
0
11
0
Order By: Relevance
“…Studies by other authors found that as GO levels increased, the concentration of H 2 O 2 decreased, which indicates that GO acts as an electron absorber in the system [ 41 ]. Moreover, GO also reacted preferentially with O 2 − [ 42 ]. Our studies also did not reveal the pro-oxidative activity of GO.…”
Section: Discussionmentioning
confidence: 99%
“…Studies by other authors found that as GO levels increased, the concentration of H 2 O 2 decreased, which indicates that GO acts as an electron absorber in the system [ 41 ]. Moreover, GO also reacted preferentially with O 2 − [ 42 ]. Our studies also did not reveal the pro-oxidative activity of GO.…”
Section: Discussionmentioning
confidence: 99%
“…Indirect photoreactions are involved in the fate of organic contaminants [ 334 338 ], nanomaterials [ 339 ], and certain pesticides [ 340 342 ]. Considering the large effects of CDOM on the inactivation rate constants of contaminants through UV protection and photosensitisation, we expect that future ozone-related changes will be much smaller than changes caused by browning of aquatic environments.…”
Section: Biogeochemical Cycles In the Environmentmentioning
confidence: 99%
“…Copyright 2017, American Chemical Society; (b) Photoluminescence excitation–emission matrices of •OH reacted GO. Adapted with the permission of ref . Copyright 2019, Royal Society of Chemistry; (c) Schematic illustration of chemical instability of GO by ozonation treatment.…”
Section: Chemical Stability and Regeneration Of Nanocarbonsmentioning
confidence: 99%